The effect of a novel weight-supported kinetic chain resistance training program on proximal core muscular endurance, trunk-to-arm muscular power, and bat swing speed - Palmer, T. G.; McCabe, M. (The Journal of Strength and Conditioning Research, 2023)
Muscular stability and muscular power at the proximal core segments of the pelvis, spine, and trunk are essential attributes in maximizing bat swing speed in the sport of softball. Weight-supported kinetic chain resistance training (WsKC) is a novel closed kinetic chain technique that provides synergistic multiplanar stressors to the proximal core segments via the lower and upper extremities while limiting joint compression and sheer forces throughout the kinetic chain. The aim of this study was to assess the effect a 7-week preseason WsKC program would have on an isometric muscular endurance plank, trunk-to-arm peak muscular power (TAPP), trunk-to-arm peak velocity (TAPV), and bat swing speed (BSS) compared with a traditional isotonic weight resistance training program. Twenty-seven female high school softball players (age = 16 years, height = 167.6 cm, body mass = 62.86 kg) were assigned in a blocked randomization to one of 2 groups: a standing weight-supported kinetic chain resistance training (WsT) group (n = 13) or a pseudo-control traditional isotonic training (TT) group (n = 14). The WsT group had significant improvements (p < 0.05) for the isometric endurance plank (p = 0.001), TAPP (p = 0.002), TAPV (p = 0.001), and BSS (p = 0.02) compared with the TT group. The training effect size (ES) was large for the WsT group for all variables (ES = 1.0-7.4) and small to moderate for a majority of the TT variables (ES = 0.06-0.47). The simultaneous improvement in the isometric endurance plank, trunk-to-arm rotations, and BSS indicates that the WsKC contributed to subsequent improvements in BSS in high school softball players.